Accuracy of prediction of birth weight by fetal ultrasound - Bajracharya, J; Shrestha, NS; Karki, C (Health Renaissance, 2012)
Introduction: Estimation of accurate fetal weight is essential in obstetrical management and we aim to see the accuracy of fetal ultrasound in estimating birth weight in our setting. Method: 150 women with full term singleton pregnancy leading to live birth were included in the study. Prenatal fetal ultrasound database was reviewed for the fetal biometry and fetal weight estimation and delivery records were reviewed for actual birth weight. Error in estimation was calculated. Result: The study showed that fetal ultrasound using Hadlock.s formula has error in estimation of fetal weight by about 290 gm ± 250 gm. In 40% of the cases, there is an error of estimation by more than 10% compared to actual weight. Conclusion: There is a significant error in the estimation of the fetal weight. Depending only on the fetal ultrasound for the estimation of fetal weight can lead to unnecessary obstetrical intervention. It is necessary to correlate the ultrasound findings with clinical examination. Health Renaissance; September-December 2012; Vol 10 (No.3);236-238 DOI: http://dx.doi.org/10.3126/hren.v10i3.7053